Dr. Freddy Castillo — Deep Plane Facelift — Lima - Castillo, Freddy (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Freddy Castillo, practicing in Lima, Peru. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003098; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; peru; lima